STRATEGI PEMBELAJARAN AKTIF UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN FIKIH KELAS XI DI MAN 4 KEDIRI - Ida Ansori (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Active learning strategy is a learning method that encourages students to be actively involved in the teaching and learning process, so that they can more easily understand and remember the material more effectively. This study aims to identify active learning strategies that are efficient in improving students' understanding, especially in the subject of Fiqh for class XI at MAN 4 Kediri. This active learning strategy has proven to be more effective because it encourages students to participate directly, increases motivation, and encourages collaboration. In addition, this method can reduce boredom caused by monotonous lecture methods, so that students become more active, creative, and innovative. Thus, educators can consider implementing active learning strategies to improve students' understanding in the subject of Fiqh